Legal status of medical marijuana - studying knowledge and opinions among pharmacy students - Magdalena Gazdowicz; Natalia Susłowska; Kamila Piątkowska; Agnieszka Ewa Zimmermann (Polish Pharmaceutical Society, 2020)
Background: Medical marijuana was legalized in Poland in 2017. Cannabinoids contained in marijuana can play a big role in the treatment of pain. The right to pain treatment is especially needed for palliative patients, as it ensures them dying in dignity and peace. With the growing occurrence of medical marijuana in the treatment of patients, future pharmacists should acquire the necessary knowledge on this topic during their studies. Pharmacists have a legal obligation to provide information on prescription medicinal products containing cannabis, including storage and use of the medicinal product dispensed, as well as precautions related to the medicinal product dispensed. Aim of the study: The study looked for answers to questions about the level of pharmacy students' knowledge concerning medical marijuana and relationship between the year of study and level of knowledge. On the basis of a medical prescription, pharmacists make prescription drugs containing medicinal hemp in pharmacies. Materials and methods: The survey study was conducted from February 25 to April 19. The studied group consisted of 132 pharmacy students from all Pharmaceutical Departments in Poland. The form contained 16 questions. Most of these questions were disjunctive and in several of them the Likert scale was used again. Results: The results of the study indicate that pharmacy students rate their knowledge of medical marijuana very low. Students do not know the indications for medical cannabis use or its side effects. The study sought to find out if there was a need for additional education for students about medical marijuana. No correlation was found between the year of study and the knowledge of pharmacy students. Conslusions: Education about endocannabinoid system in the course of pharmacy studies is negligible, therefore there is an increased need to include this topic in the pharmaceutical study program. Regardless of the year of study, the level of pharmacy students' knowledge about indications, side effects or how to take medical marijuana is low and they need additional education in this field